ELIMINATION METHOD

Elimination method :

Here we are going to see how to solve any linear equation by using this method.

Steps in Elimination Method

In the given linear equations we can eliminate any one of the variables.

The flow chart given below represents, what are the steps to be done in this method.

Elimination method - Examples

Let us consider the example below to understand this topic better

Question 1 :

Solve by elimination method

3 x + 4 y = -25

2 x - 3 y = 6

Solution :

3 x + 4 y = -25 ---- (1)

2 x - 3 y = 6  ---- (2)

Since the coefficients are different, we have to find the common number for 4 and 3.The common number for 4 and 3 is 12.

(1) x 3 => 9 x + 12 y = -75

(2) x 4 => 8 x - 12 y = 24

Since the signs are different, we have to add equation for eliminating y.

(1) + (2)         9 x + 12 y  =  -75

                       8 x - 12 y  =  24

                       -------------------

                        17 x  =  - 51

                             x  =  -51/17

                             x  =  -3

Apply x  =  -3 in the first equation

 3 (-3) + 4 y  =  -25

- 9 + 4 y  =  -25 

4 y  =  -25 + 9

4 y  =  -16

y  =  -16/4

y  =  -4

Solution :

      x = -3

      y = -4

By applying the solution in the given equation, we may verify the solution.

3 (-3) + 4 (-4) = -25

 -9 - 16 = -25

- 25 = -25

So, we can decide the answer what we got is correct.

Question 2 :

Solve by elimination method

2 x + 3 y = 5

3 x + 4 y = 7

Solution :

2 x + 3 y = 5  ---- (1)

3 x + 4 y = 7  ---- (2)

The coefficients of x and y are different.Since the symbols of x terms and y terms are same, we can eliminate either x or y term.

So, we are going to eliminate "y" for that we have to find the L.C.M for 3 and 4.The L.C.M for 3 and 4 is 12.

(1) x 4 => 8 x + 12 y = 20

(2) x 3 => 9 x + 12 y = 21

Since the signs are same we have to subtract the 2nd equation from 1st equation equation for eliminating y.

(1) - (2)          8 x + 12 y = 20

                      9 x + 12 y = 21

                      (-)    (-)      (-)

                    -------------------

                        -1 x = - 1

                             x = -1/(-1)

                             x = 1

Substitute x = 1 in the first equation

8 (1) + 12 y = 20

8 + 12 y = 20 

12 y = 20 - 8

12 y = 12

 y = 12/12

y = 1

Solution :

      x = 1

      y = 1

By applying the solution in the given equation, we may verify the solution.

          8 x + 12 y = 20

          8(1) + 12 (1) = 20

                 20 = 20

So we can decide the answer what we got is correct.

Elimination method worksheet contains some practice questions based on this topic.You can also try that.

Related topics

After having gone through the stuff, we hope that the students would have understood "Elimination method"

Apart from the stuff given above, if you want to know more about "Elimination method", please click here

Apart from the stuff given in this section, if you need any other stuff in math, please use our google custom search here.

Widget is loading comments...